The Effectiveness of Bappeda's Role in Medan City Original Revenue Planning - Diah Ayu Agustin; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This type of research is descriptive research that focuses on the effectiveness of the role of Bappeda in planning local revenue in Medan City. This study aims to determine the effectiveness of the role of Bappeda in planning the regional original income of the city of Medan. The data is sourced directly from the Bappeda of Medan City and is of the secondary data type. Furthermore, secondary data in question is data regarding the effectiveness of the role of Bappeda in planning local revenue for Medan City. While the secondary qualitative data in question is a reference to several books that concern and support this research. The results of the study indicate that in carrying out its role in terms of planning for increasing the local original tax (PAD) of Medan City, it is still not fully effective, so there needs to be steps or strategies that must be carried out by the Medan City Bappeda such as improving the quality of planning and development documents through strengthening coordination between sectors. development as well as improving the quality of measurement of performance indicators. This is also supported by exploring the potential of the field, counseling about taxpayers, re-collecting data and coordinating with related parties.